Nanoparticles for cosmetic use and its application - Chiari-Andréo, Bruna Galdorfini [UNESP]; De Almeida-Cincotto, Maria Gabriela José [UNESP]; Oshiro, João Augusto [UNESP]; Taniguchi, Cibele Yumi Yamada [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Isaac, Vera Lucia Borges [UNESP] (Elsevier, 2019)
Nanoparticles have been cited as a tool to solve many pharmaceutical problems, also in the cosmetic field. Some advantages in using them are to vectorize or retard the release and action of a cosmetic active substance, to increase stability, effectiveness, and safety, etc. However, there are many kinds of nanoparticles that should be chosen accordingly to the need of application. Although there are advantages related to the use of nanoparticles, some difficulties could be cited, such as the scale up of the technology and safety assessment. Considering the above, this chapter aimed to show the main kinds of nanoparticles employed in the cosmetic area, highlighting the advantages obtained with their use. Also, it will discuss the scale-up and the safety assessment, mainly in relation to the pathway followed by the nanoparticle when applied on the skin.
Keywords: Cosmetics; Efficacy; Innovation; Nanotechnology; Safety